VD_FINDINFO Pron / 2011 / 138 vom 7. Dezember 2011 - VD Tribunal cantonal (2011)
AVANCE DE FRAIS, ASSURANCE COMPLÉMENTAIRE, LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE | 103 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 321 al. 1 CPC (CH)